2018
DOI: 10.1016/j.ccell.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Therapeutic Targets in Rhabdomyosarcoma through Integrated Genomic, Epigenomic, and Proteomic Analyses

Abstract: Personalized cancer therapy targeting somatic mutations in patient tumors is increasingly being incorporated into practice. Other therapeutic vulnerabilities resulting from changes in gene expression due to tumor specific epigenetic perturbations are progressively being recognized. These genomic and epigenomic changes are ultimately manifest in the tumor proteome and phosphoproteome. We integrated transcriptomic, epigenomic, and proteomic/phosphoproteomic data to elucidate the cellular origins and therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 74 publications
10
138
0
Order By: Relevance
“…To gain insights into a possible role of DDX5 in RMS, we looked at its expression and epigenetic status through the Integrated Rhabdomyosarcoma database of the St. Jude Children's Research Hospital (https://pecan.stjude.cloud/proteinpaint/study/RHB2018) (14). Among the 18 chromatin hidden Markov modeling (chromHMM) states (15) identified in the study (14) (Supplemental Figure. 1A), DDX5 showed a strong active transcription start site (TSS) (red bars) and an actively transcribed gene body (green bars) in either normal myoblasts and myotubes, and primary ERMS and ARMS samples (Supplemental Figure 1B).…”
Section: Ddx5 Is Overexpressed In Rhabdomyosarcoma and Sustains Fp-armentioning
confidence: 99%
“…To gain insights into a possible role of DDX5 in RMS, we looked at its expression and epigenetic status through the Integrated Rhabdomyosarcoma database of the St. Jude Children's Research Hospital (https://pecan.stjude.cloud/proteinpaint/study/RHB2018) (14). Among the 18 chromatin hidden Markov modeling (chromHMM) states (15) identified in the study (14) (Supplemental Figure. 1A), DDX5 showed a strong active transcription start site (TSS) (red bars) and an actively transcribed gene body (green bars) in either normal myoblasts and myotubes, and primary ERMS and ARMS samples (Supplemental Figure 1B).…”
Section: Ddx5 Is Overexpressed In Rhabdomyosarcoma and Sustains Fp-armentioning
confidence: 99%
“…There are increasing numbers of studies analysing molecular changes in RMS, including proteome and epigenetic changes, and it has recently been found that ARMS occurs in more differentiated cells than ERMS, and that in RMS not only RAS /MEK/ERK/CDK4/6 pathway is deregulated, but there are also disorders in the so-called Unfolded Protein Response (pathway associated with the reaction to the accumulation of improperly folded proteins) and in mitosis between the G2 and M stage [68].…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
“…A recent preclinical study showed that combination of the Hsp90 inhibitor Ganetespib with Vincristine (VCR) and Irinotecan (IRN) significantly enhanced the tumor response in RMS xenograft models 43 . Considering that Ganetespib alone showed no significant effect on inhibition of RMS xenograft 43 while 17-DMAG significantly delayed tumor growth ( Fig.…”
Section: Combination Of 17-dmag With Conventional Chemotherapy or Bromentioning
confidence: 99%